(untitled) (Malaysian Journal of Applied Linguistics (MJoAL), 2023)
In contrast to being on record, speakers in Shariah-based Reconciliation Case Proceedings (RCP) normally do the Face Threatening Acts (FTA) off record strategy if they intend to convey their meaning to an addressee in an ambiguous ways or hinting manner. Thus, the aim of this paper is to explore the use of Figurative and Idiomatic Expressions (FIE) in the RCP. The study utilized 12 various cases on Family Dispute Marital Issues (FDMI) and the data was obtained through audiovisual recordings in Bauchi State Sharia Commission (BSSC) in Nigeria. The data were coded and analysed using Nvivo, focusing on Brown and Levinson’s Off-Record strategy as part of the conditions in determining the choice of politeness strategy. The study showed that FIE FTA off record strategy was richly used across the 12 cases. However, the FIE were mostly employed by court officials in the attempt to avoid being perceived as bias or unfair to other parties during RCP. A total of 24 participants used 75 Interactive Turn-Takings (ITT). The findings revealed the use of various kinds of FIE FTA off record strategies including metaphors, personifications, climax, anti-climax, metonymy, hyperbole, and euphemism among others. The findings also indicated that sarcasm was used by the court officials to address or query the actions of addressee/s. Disputing parties were found of using metonymy, hyperbole to exaggerate their claims and euphemism in expressing unpleasant information in the attempt to establish defences. Finally, the paper demonstrates that it is a cultural practice of the speakers in Shariah-based RCP to use FIE in the quest to achieve settlement of matrimonial and family disputes. The implications of this study were also discussed on adoption and teaching of FIE in shariah legal schools to enhance the quality of RCP in Shariah-based courts. The paper also recommends further studies on other aspects of sociopragmatic acts of RCP to improve the value of Shariah-based courts of Nigeria and the world at large for the benefit of mankind.